The Impact of The Main Characteristics of Accounting Information on Improving Corporate ‎Sustainability - Khogly, Mohamed Elnair Mohamedain (International Journal of Accounting and Economics Studies, 2025)
The study aims to provide a concrete framework that enables Saudi industrial companies in the ‎Eastern Province to significantly improve their operational efficiency and current performance, as ‎well as enhance their ongoing resilience and long-term sustainability. Primary data were collected ‎primarily through the distribution of a structured questionnaire, conducted as part of a ‎comprehensive survey. This survey targeted a large and diverse sample of 321 industrial ‎companies. The study used partial least squares structural equation modeling (PLS-SEM), a ‎powerful multivariate statistical technique suitable for examining complex causal relationships and ‎testing theoretical models using latent variables. The study results indicate that the key ‎characteristics of accounting information play a significant role in improving the economic, ‎environmental, and social performance of the industrial sector in the Kingdom of Saudi Arabia. ‎The results confirm that through this accounting information and its strategic adaptation, industrial ‎companies can not only enhance their financial viability and operational efficiency, but also ‎significantly reduce their environmental footprint and enhance their social responsibility. The ‎specialized knowledge of strategic planners enables them to make predictions to improve ‎economic, environmental, and social sustainability by linking them to accounting information. This ‎study encourages strategic decision-makers in industrial companies in Saudi Arabia to strive to ‎improve the relevance and reliability of accounting information and maximize the sustainability of ‎their economic, environmental, and social performance‎.